GEOLOGICAL FACTORS INFLUENCING SOIL ERODIBILITY IN PARTS OF SOUTHEASTERN NIGERIA - Okeke, Adaobi N; Uche , Obinna T (International Journal of Civil Engineering and Architecture and Real Estate, 2024)
This study focuses on analyzing soil erodibility in five Local Government Areas (LGAs) in Imo State, Nigeria: Isu, Mbaitoli, Njaba, Orlu, and Oru East. These areas are prone to flooding due to their location within the lower Niger River Basin, exacerbating soil erosion. The study aims to evaluate geological and soil characteristics influencing landslide susceptibility in these LGAs. The aim of this study is to assess soil erodibility factors and geological characteristics in Imo State, Nigeria, focusing on Isu, Mbaitoli, Njaba, Orlu, and Oru East LGAs. It involves identifying predominant soil types, calculating Soil Erodibility Factor (K), and mapping erosion susceptibilities. The study correlates data with hydrological and climatic information to analyze landslide risks and propose mitigation strategies. This study utilizes data primarily from the Soil Map of the World, version 3.6, corrected for errors and updated for relevance. Geographic Information System (GIS) tools are employed for spatial analyses, including mapping soil types and erosion susceptibilities. The study also integrates topographical data to understand elevation variations and geological formations impacting soil characteristics. The study identifies two primary soil types: Dystric Nitosols covering 578.63 km² and Xanthic Ferralsols covering 0.064 km². Dystric Nitosols have a low Soil Erodibility Factor (K) of 0.017769 t.ha.h.ha/MJ/mm, indicating good structural stability and less susceptibility to erosion. In contrast, Xanthic Ferralsols exhibit a higher K-factor of 0.018724 t.ha.h.ha/MJ/mm, suggesting greater vulnerability to erosion due to their acidic nature and lower fertility. The spatial distribution of soil types and their erodibility factors highlights significant implications for agricultural productivity and environmental conservation. Dystric Nitosols, with their high fertility and good structure, support diverse crops and ecosystems. Effective management practices such as crop rotation and cover cropping are essential for sustaining their productivity. In contrast, Xanthic Ferralsols require intensive management to mitigate erosion risks and improve soil fertility through techniques like contour plowing and organic amendments. This study's comprehensive analysis of soil erodibility, topography, and geological characteristics provides insights crucial for sustainable land management and agricultural planning in Imo State, Nigeria. Implementing tailored soil conservation strategies is essential to maintain soil health, enhance agricultural productivity, and support ecological balance in the region. The novelty of this study lies in its detailed assessment of soil erodibility factors across distinct geological formations in Imo State, Nigeria. By integrating GIS analyses with empirical data, the study offers precise recommendations for mitigating landslide risks and preserving soil integrity amidst challenging environmental conditions.